Protocolo de consulta prévia: instrumento de diálogo e de fortalecimento das comunidades quilombolas do Maicá, Santarém - PA - SARMENTO, Ana Maria Silva (Universidade Federal do Oeste do Pará, 2021)
The increasing construction of prior consultation protocols of the traditional communities of the Amazon region has shown that these instruments are a response to the administrative and legislative decisions edited without considering the right of the communities affected by these decisions to be heard. The violation of the right to the Prior Consultation, Free and Informed (PCFI) contained in Convention no. 169 of the Labor International Organization (LIO), 1989, that causes traditional communities to provoke domestic courts and international courts to respect their right to participate in decision-making that affects them directly. The intention in writing this thesis is to answer the following question: how did the construction of the protocol of prior consultation of the Federation of Quilombola Organizations of Santarém (FQOS) strengthen the dialogue among the associated communities and how did it serve to make resistant the quilombola movement in Santarem? For this, the methodology used allowed the analysis of the results of the data collected through interviews using the Collective Subject Discourse (CDS), by Lefrève and Lefrève (2005). The process of constructing the prior consultation protocol for remnants of quilombo communities associated with FQOS happened because of a mutual understanding resulting from the rational adherence of all to a statement, free of manipulations or communications distorted by external agents, based on common convictions. The participation of the quilombola communities was effective and supported in the dialogue, in the communicative action by means of which the agreements and consensuses were obtained considering the equal of right of participation of all individuals involved, which not only promoted the approach of the communities quilombolas, but its strengthening before the spaces of debates. The FQOS prior consultation protocol proved to be a strong instrument of participation in different issues affecting the rights of quilombos remnants, also revealing a new form of use and meaning.